Differential effects of hormone therapy on serotonin, vascular function and mood in the KEEPS. (2nd January 2016) - Raz, L.; Hunter, L. V.; Dowling, N. M.; Wharton, W.; Gleason, C. E.; Jayachandran, M.; Anderson, L.; Asthana, S.; Miller, V. M.
Abstract: Background Serotonin (5-hydroxytryptamine, 5-HT) is modulated by sex steroid hormones and affects vascular function and mood. In the Kronos Early Estrogen Prevention Cognitive and Affective Ancillary Study (KEEPS-Cog), women randomized to oral conjugated equine estrogens (oCEE) showed greater benefit on affective mood states than women randomized to transdermal 17β-estradiol (tE2) or placebo (PL). This study examined the effect of these treatments on the platelet content of 5-HT as a surrogate measure of 5-HT synthesis and uptake in the brain. Methods The following were measured in a subset ( n = 79) of women enrolled in KEEPS-Cog: 5-HT by ELISA, carotid intima-medial thickness (CIMT) by ultrasound, endothelial function by reactive hyperemic index (RHI), and self-reported symptoms of affective mood states by the Profile of Mood States (POMS) questionnaire. Results Mean platelet content of 5-HT increased by 107.0%, 84.5% and 39.8%, in tE2, oCEE and PL groups, respectively. Platelet 5-HT positively correlated with estrone in the oCEE group and with 17β- estradiol in the tE2 group. Platelet 5-HT showed a positive association with RHI, but not CIMT, in the PL and oCEE groups. Reduction in mood scores for depression-dejection and anger-hostility was associated with elevations in platelet 5-HT only in the oCEE group ( r = −0.5, p = 0.02). Conclusions Effects of oCEE compared to tE2 on RHI and mood may be related to mechanisms involving platelet, and perhaps neuronal, uptake and release of 5-HT and reflect conversion of estrone to bioavailable 17β-estradiol in platelets and the brain.